Efektivitas Layanan Bimbingan Kelompok dengan Menggunakan Teknik Group Exersice untuk Meningkatkan Kemandirian Belajar - Arnik Agniya Fikriyah, - (2023)
ABSTRACT Arnik Agniya Fikriyah. (2022). The Effectiveness of Group Guidance Services with Group Exercise Techniques to Increase Learning Independence (Quasi-Experimental Research on Students at MAN 3 Ciamis Academic Year 2022/2023). The research is motivated by the phenomenon that students have learning independence problems as indicated by some students not confident in their abilities, still dependent on others, having difficulty studying independently, following friends' work, and lacking the initiative to ask questions when there is learning material that is not yet understood. With this phenomenon, group guidance services with group exercise techniques are an alternative to increasing learning independence. The research aims to test the effectiveness of group guidance services using group exercise techniques to increase student learning independence. The research approach uses a quantitative approach with a research design, namely Quasi Experiment Model Nonequivalent Control-Group Design using Pretest-Posttest. The research population is class XI for the 2022/2023 Academic Year of MAN 3 Ciamis. The research sample consisted of 16 people consisting from 8 experimental groups and 8 control groups who were taken using a simple random sampling technique. Analysis of research data using non-parametric statistical tests Mann Whitney U Test. The results of the study showed that the group guidance using the group exercise technique was effective in increasing the learning independence of students with a significance value of 0.001. Keywords: Independent Learning, Students, Group Guidance